The experience of a slave in South Carolina - Jackson, John Andrew (University of North Carolina at Chapel Hill Library : Distributed by University of North Carolina at Chapel Hill Press, 2011)
In The Experience of a Slave in South Carolina, escaped slave John Andrew Jackson seeks to educate his readers on the horrors of slavery. He spares no details in relating the murder of his sister, the separation of his family, and his own frequent whi.